Efect of palm oil factory sludge manure on the growth and yield of cabbage - Sebayang, Lukas (Jurnal Online Pertanian Tropik, 2019)
Palm sludge is a source of organic material potential to increase cabbage production. The research was conducted at Berastagi Sub Research Institute for Horticulture at 1.230 m above sea level on September 2017 to January 2018. The purpose of this study was to determine the effect of palm oil factory sludge manuring on cabbage growth and yield. The experiment used Randomized Block Design with 5 replications. The results indicated that treatment of NPK + Cattle manure at 30 tons/ha was the highest yield (73.4 tons/ha) followed by treatment NPK + Palm Oil Factory Sludge at 15 tons/ha ( 69.6 tons/ha). The used of fertilizer combination of NPK + Palm Oil Factory Sludge at 15 tons/ha was recommended.